2015
DOI: 10.18632/oncotarget.4212
|View full text |Cite
|
Sign up to set email alerts
|

The splicing modulator sudemycin induces a specific antitumor response and cooperates with ibrutinib in chronic lymphocytic leukemia

Abstract: Mutations or deregulated expression of the components of the spliceosome can influence the splicing pattern of several genes and contribute to the development of tumors. In this context, we report that the spliceosome modulator sudemycin induces selective cytotoxicity in primary chronic lymphocytic leukemia (CLL) cells when compared with healthy lymphocytes and tumor cells from other B-lymphoid malignancies, with a slight bias for CLL cases with mutations in spliceosome-RNA processing machinery. Consistently, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 50 publications
(81 reference statements)
3
46
0
Order By: Relevance
“…Recent studies have suggested that cancers with spliceosome gene mutations may have an increased sensitivity to splicing modulator drugs like sudemycin;323334 this study provides further evidence to support this hypothesis. Specifically, we show that mutant U2AF1 cells are sensitive to in vivo treatment with sudemycin.…”
Section: Discussionsupporting
confidence: 70%
“…Recent studies have suggested that cancers with spliceosome gene mutations may have an increased sensitivity to splicing modulator drugs like sudemycin;323334 this study provides further evidence to support this hypothesis. Specifically, we show that mutant U2AF1 cells are sensitive to in vivo treatment with sudemycin.…”
Section: Discussionsupporting
confidence: 70%
“…88 Primary human MDS/AML cells with mutant U2AF1 had impaired proliferation after treatment with SD1 in vitro compared with cells lacking splicing factor mutations and in vivo treatment of mice with SD6 reverted aberrant hematopoietic progenitor expansion in an inducible mouse model of mutant U2AF1. 89 FD-895 caused induction of apoptosis in CLL cells in vitro (independent of SF3B1 genotype) at nanomolar concentrations, similar to PB.…”
Section: Splicing Modulatorsmentioning
confidence: 95%
“…Further efforts are needed to determine whether this was an on- or off-target effect of U2 snRNP inhibition in vivo . In the meantime, several preclinical studies are evaluating the utility and safety of sudemycins 156,157 for cancer therapy.…”
Section: Implications For Therapymentioning
confidence: 99%